(untitled) (Jurnal Mekanikal, 2018)
The mode of transporting crude oil via pipelines was understood to have a potential for a very large volume of fluids to be released from the pipeline system. This incindent will pose its small but finite risk to both population and environment along the route. This paper discusses the potential hazards usually encountered in the transporting crude oil using pipeline. The risk , consequence. and risk reducing measures are also presented It is found that the pipeline mode of transporting crude is safe and reliable. Fatalities per ton-kilometer transported are much lower than for any other means of transportation.